Hemoglobin mass does not increase in able-bodied individuals after consecutive days of acute intermittent hypoxia - Harding, Andrew S.; Noyes, Katelyn D.; Pollet, Aviva K.; Kim, Sewan; Tan, Andrew Q. (Frontiers in Physiology, 2025)
Prolonged exposure to hypoxia can elevate serum erythropoietin (EPO) and may eventually increase hemoglobin mass. However, whether intermittent hypoxia consisting of breathing short intervals alternated with normoxia (acute intermittent hypoxia; AIH) can trigger erythropoiesis and lead to increases in hemoglobin mass is less clear. Therefore, the purpose of this study was to investigate the effect of consecutive days of AIH on hemoglobin mass. Participants (n = 18) were exposed to 4 consecutive days of AIH consisting of fifteen 90 s intervals of breathing ∼9% O2 alternating with 60 s of breathing room air (∼21% O2). Hemoglobin mass was measured in each participant before the first and after the last exposure. In a separate group of individuals (n = 12) we collected serum blood samples for EPO analysis before and 4.5 h after one of the AIH sessions, as well as at the same timeframe on a day with no AIH to serve as control. There was no significant increase in hemoglobin mass after four consecutive days of AIH in the first group with no serum EPO collection, or in the second group for which we collected EPO. Further, there was no significant increase in serum EPO after AIH as compared to control. These results indicate that four consecutive days of AIH is not a sufficient hypoxia exposure to elicit increases in hemoglobin mass in able-bodied individuals. Serum EPO results suggest that a single session of the current acute intermittent hypoxia protocol does not provide enough stimulus for EPO production.